2022
DOI: 10.1109/access.2022.3216601
|View full text |Cite
|
Sign up to set email alerts
|

Energy-Efficient Local Path Planning of a Self-Guided Vehicle by Considering the Load Position

Abstract: The local path planning, as one of the navigation stages, plays a significant role in the energy consumption of Self-Guided Vehicles (SGV). Since SGV must operate for several hours on a single battery charge to transport loads, its energy consumption is a critical issue. Therefore, this article puts forward an approach for boosting the energy efficiency of the local path planning stage using load position. Unlike other similar works which solely use robots' kinematic and kinetic constraints to develop energy-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The center of mass is fundamental in physics and engineering, significantly affecting robotic systems' energy consumption. Mohammadpour et al (2022) proposed a path-planning algorithm considering the center of mass. Their research emphasizes the impact of centroid displacement on self-guided vehicles' (SGVs') energy consumption, showing that payload placement alters the SGV's dynamic inertial parameters and shifts the center of mass, affecting energy consumption during rotational motion.…”
Section: Impact Of the Center Of Massmentioning
confidence: 99%
“…The center of mass is fundamental in physics and engineering, significantly affecting robotic systems' energy consumption. Mohammadpour et al (2022) proposed a path-planning algorithm considering the center of mass. Their research emphasizes the impact of centroid displacement on self-guided vehicles' (SGVs') energy consumption, showing that payload placement alters the SGV's dynamic inertial parameters and shifts the center of mass, affecting energy consumption during rotational motion.…”
Section: Impact Of the Center Of Massmentioning
confidence: 99%
“…Fadlo et al (2021) proposed an energy consumption model for differential‐wheeled mobile robots using fuzzy logic control. Mohammadpour et al (2022) studied the robot's load position and proposed an energy optimization method based on local path planning. Liu et al (2021) proposed an improved path‐planning algorithm based on the A* algorithm and modeled the robot's energy consumption using an energy model.…”
Section: Introductionmentioning
confidence: 99%
“…However, several works have been proposed to incorporate fundamental safety criteria among the most commonly used local motion planners for SGV application namely: Dynamic Window Approach (DWA) [24], Artificial Potential Field (APF) [25], and Timed Elastic Bands (TEB) [26]. Dynamic model-based DWA optimization is considered in [27]. The authors have demonstrated that the position of the center of mass affects the motion stability of the mobile platform.…”
Section: Introductionmentioning
confidence: 99%